Establishment and Development of the First Biobank of Inflammatory Bowel Disease, Suspected to Primary Immunodeficiency Diseases in Iran - Sherkat, Roya (Adv Biomed Res, 2018)
BACKGROUND: Inflammatory bowel disease (IBD) might be an immunodeficiency rather than an excessive inflammatory reaction. IBD, suspected to primary immunodeficiency diseases biobank (IBDSPIDB) as a resource for researches can help improve the prevention, diagnosis, and illness treatment and the health promotion throughout the society. Therefore, we launched the biobank of IBDSPID for the first time in Iran. MATERIALS AND METHODS: This study was designed to provide the IBDSPIDB to have a high-quality DNA, RNA, and cDNA. Among of 365 patients, 39 have inclusion criteria that were as below: (1) IBD diagnosis before 5 years of age. (2) Resistance to conventional therapy of IBD. (3) Severe IBD. (4) Signs of SPID (including ear infections or pneumonia or recurrent sinus within the 1-year period; failure to thrive; poor response to the prolonged use of antibiotics; persistent thrush or skin abscesses; or a family history of PID). RESULTS: Out of 39 patients, 51.3% were males. The mean age was 32.92 ± 15.90 years old. Ulcerative colitis (79.5%) was more than Crohn's disease. The majority of patients (50.0%) had severe IBDSPID. Resistance to drugs and consanguinity was 12.9% and 47.4%, respectively. Age at onset in 65.8% of patients was after 17 years old. Patients with autoimmune, allergy, and immunodeficiency disease history were 33.3%, 33.3%, and 10.36%, respectively. RNA and cDNA yields large quantities of high-quality DNA obtained and stored. CONCLUSION: Our biobank would be valuable for future genetic and molecular study to be more about the relation between IBD and PID.